Rethinking childhood - Pufall, Peter B.; Unsworth, Richard P. (New Brunswick, N.J. : Rutgers University Press, 2004)
In Rethinking Childhood, twenty contributors, coming from the disciplines of anthropology, government, law, psychology, education, religion, philosophy, and sociology, provide a multidisciplinary view of childhood by listening and understanding the ways children shape their own futures. Taken together, these essays develop a new paradigm for understanding childhood as children experience these years. This paradigm challenges readers to develop fresh ways of listening to children's voices that enable both children and adults to cross the barriers of age, experience, and stereotypi.
Preface ; Introduction: the imperative and the process for rethinking childhood / Peter B. Pufall and Richard P. Unsworth -- pt. I. Children's voice and agency. Understanding childhood from an interdisciplinary perspective: problems and potentials / Allison James ; Children as philosophers / Gareth B. Matthews ; Children as theologians / Eileen W. Lindner ; Action, voice and identity in children's lives / Jack A. Meacham -- pt. II. Voice and agency in education. "Do you know you have worms on your pearls?": Listening to children's voices in the classroom / Susan Etheredge ; Cultural integrity and schooling outcomes of African American children from low-income backgrounds / A. Wade Boykin and Brenda A. Allen ; "We have these rules inside": the effects of exercising voice in a children's online forum / Justine Cassell -- pt. III. Voice and agency within families. Advertising and marketing to children in the United States / Enola G. Aird ; Children's lives in and out of poverty / Karen A. Gray ; Children of divorce / Jan Pryor and Robert E. Emery -- pt. IV. Voice and agency in neighborhoods and sports. Negotiating the dance: social capital from the perspective of neighborhood children and adults / James C. Spilsbury and Jill E. Korbin ; Are we having fun yet? / Rhonda Singer -- pt. V. Voice and agency as legal rights. Re-visioning rights for children / Barbara Bennett Woodhouse ; Recognizing the roots: children's identity rights / Alice Hearst -- Resources for further research: a roadmap for surfing the Internet / Raymond A. Ducharme.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Children; Children -- Social conditions; Enfants -- Conditions sociales; SOCIAL SCIENCE -- Children's Studies; Children; Children -- Social conditions; Samfundsvidenskab -- Sociologi